Common Repeat Elements in the Mitochondrial and Plastid Genomes of Green Algae - Smith, David Roy (Frontiers in Genetics, 2020)
Despite both originating from endosymbiotic bacteria, one does not typically expect mitochondrial DNA (mtDNA) to show strong sequence identity to plastid DNA (ptDNA). Nevertheless, a recent analysis of Haematococcus lacustris revealed exactly that. A common repeat element has proliferated throughout the mtDNA and ptDNA of this chlamydomonadalean green alga, resulting in the unprecedented situation whereby these two distinct organelle genomes are largely made up of nearly identical sequences. In this short update to the work on H. lacustris, I highlight another chlamydomonadalean species (Stephanosphaera pluvialis) for which matching repeats have spread throughout its organelle genomes. What’s more, the organelle repeats from S. pluvialis are similar to those from H. lacustris, suggesting that they have a shared origin, and perhaps existed in the mtDNA and ptDNA of the most recent common ancestor of these two species. However, my examination of organelle genomes from other close relatives of H. lacustris and S. pluvialis did not uncover further compelling examples of common organelle repeat elements, meaning that the evolutionary history of these repeats might be more complicated than initially thought.